Left ventricular global longitudinal strain is predictive of all-cause mortality independent of aortic stenosis severity and ejection fraction. (28th July 2017) - Ng, Arnold C T; Prihadi, Edgard A; Antoni, M Louisa; Bertini, Matteo; Ewe, See Hooi; Ajmone Marsan, Nina; Leung, Dominic Y; Delgado, Victoria; Bax, Jeroen J
Abstract: Aims: Left ventricular (LV) global longitudinal strain (GLS) may identify subclinical myocardial dysfunction in patients with aortic stenosis (AS). The aims of the present retrospective single centre study were to determine the independent prognostic value of LV GLS over LV ejection fraction (EF) and the role of LV GLS to further risk stratify severe AS patients before aortic valve replacement. Methods and results: A total of 688 patients (median age 72 years, 61.2% men) with mild ( n  = 130), moderate ( n  = 264) and severe AS ( n  = 294) were included. LV GLS was determined by 2D speckle tracking echocardiography. A total of 114 (16.6%) patients died before surgery during the study. When patients with severe AS and normal LVEF were dichotomized based on the median LV GLS value (−14.0%), patients with normal LVEF and 'preserved' LV GLS of ≤ −14% had significantly higher survival than patients with 'impaired' LV GLS of > −14%. There was no difference in survival between patients with normal LVEF but 'impaired' LV GLS ( > −14%) and patients with impaired LVEF (log-rank P  = 0.34). LV GLS was independently associated with all-cause mortality on multivariable Cox regression analysis (hazard ratio 1.17, 95% confidence interval 1.09–1.26; P  < 0.001). Conclusion: LV GLS is independently associated with all-cause mortality in AS patients. It can further risk stratify severe AS patients and may influence the optimal timing of aortic valve replacement.